The Role Of Mental Health Literacy And Dicipline In Improving The Learning Achievement Of Sports Students - Karim, Naufal Nur Fadhillah; Hidayat, Yusuf; Hambali, Burhan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to examine the perspective of mental health literacy and discipline on improving the learning achievement of sports students. This study has three main variables: Mental health literacy, Discipline, and Learning Achievement. This research was conducted using quantitative methods by distributing Gform questionnaires to 329 respondents of sports students from various study programs at the Faculty of Sports and Health Education, Universitas Pendidikan Indonesia. Mental Health Literacy Questionnaire-Young Adult Form (MHLq-YA), F.I.R.S.T. (Focus, Intention, Responsibility, Structure, Time) and Grade Point Average (IPK) were used as instruments in this study. All data obtained were analyzed through the SPSS program with correlation and multiple regression hypothesis testing. The results show a significant relationship and influence between discipline and the learning achievement of sports students. In comparison, mental health literacy and learning achievement of sports students did not show statistical significance. In conclusion, research development is needed to improve the causal relationship with the sample's demographic characteristics to produce a more optimal interpretation.